1999
DOI: 10.3758/bf03206897
|View full text |Cite
|
Sign up to set email alerts
|

Perceived area and the luminosity threshold

Abstract: Observers made forced-choice opaque/luminous responses to targets of varying luminance and varying size presented (1) on the wall of a laboratory, (2) as a disk within an annulus, and (3) embedded within a Mondrian array presented within a vision tunnel. Lightness matches were also made for nearby opaque surfaces. The results show that the threshold luminance value at which a target begins to appear self-luminous increases with its size, defined as perceived size, not retinal size. Moregenerally,the larger the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 23 publications
2
35
3
Order By: Relevance
“…All observers reported that they could perceptually organize the trapezoidal target in such a way so that it appeared as a rectangle, but when asked if the target was really a rectangle, they all agreed that it was not. These results are in agreement with those obtained by Bonato and Gilchrist (1999); however, their subjects had other depth cues available to them (stereopsis, accommodation, and convergence), whereas depth information in our displays was provided entirely by pictorial cues-namely, linear perspective and a texture gradient.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…All observers reported that they could perceptually organize the trapezoidal target in such a way so that it appeared as a rectangle, but when asked if the target was really a rectangle, they all agreed that it was not. These results are in agreement with those obtained by Bonato and Gilchrist (1999); however, their subjects had other depth cues available to them (stereopsis, accommodation, and convergence), whereas depth information in our displays was provided entirely by pictorial cues-namely, linear perspective and a texture gradient.…”
Section: Resultssupporting
confidence: 82%
“…Bonato and Gilchrist (1999) attempted to make a target more groundlike by placing a decrement (darker than its surround) in the target's center. Contrary to the results of the present Experiment 1,their target, which was the background to a square, had a lower luminosity threshold than a homogenous target.…”
Section: Square Condition Trapezoid Conditionmentioning
confidence: 99%
“…Bonato and Gilchrist (1999) showed that a white surround was seen as off-white regardless of the actual luminance of a small incremental square sitting on it (solid triangles in Figure 14). However, the lightness of the same surround was an inverse function of the square's luminance when the incremental target square was much larger (solid circles in Figure 14).…”
Section: Effect Of Size On the Luminosity Thresholdmentioning
confidence: 99%
“…Shrinking the incremental square (highest local luminance) has two consequences: first, it decreases the weight of the HL step (here, from 1.5 to 1); second, it increases the weight of the surround step (here, from 1 to 17). In the experiment by Bonato and Gilchrist (1999), reflectance matches were made to a separately illuminated Munsell scale on white, where white had a reflectance of 90% and a luminance of 539 cd/m 2 . Therefore, this white on the Munsell scale was the highest peripheral luminance (Lh).…”
Section: Rationale Of Double Anchoringmentioning
confidence: 99%
See 1 more Smart Citation